The labour market entry and integration of refugees and other migrants in Austria - Stefan Jestl; Maryna Tverdostup (The Vienna Institute for International Economic Studies (wiiw), 2023)
This paper analyses the labour market entry of refugees and other (non-humanitarian) migrants originating from middle- and low-income non-European countries that arrived in Austria in 2014-2016. Specifically, we analyse factors that shaped the transition to and out of the first job in the Austrian labour market, document the characteristics of the first job and explore job stability in Austria. Even though refugees took longer to find a job, individual and household characteristics, as well as labour market indicators, are associated with the time between arrival and the first job in Austria, similar to other migrants. Refugees and other migrants also found similar job types as their entry jobs, which tended to be located in low-wage segments. The results, however, suggest that other migrants held their first job, on average, for a longer time than refugees. Although other migrants quit their first job relatively quickly when it was marginal employment, refugees tended to hold marginal jobs as long as full-time and parttime jobs. Finally, our results suggest that entry jobs with a higher quality in terms of working hours and wages (i.e. full-time jobs) tended to be linked with job stability, while entry jobs with a lower quality (i.e. marginal jobs) tended to be associated with job instability for both refugees and other migrants. The results of the paper showcase the importance of immediate access to various training and re-education programs for refugees to improve the quality of their entry jobs and their long-term prospects in the Austrian labour market.
Keywords: C41; J15; J62; 330; Refugees; labour market integration; labour market entry; labour market transition; job stability